2017
DOI: 10.1111/cns.12696
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‐related peptide (CGRP): A novel target for Alzheimer's disease

Abstract: Alzheimer's disease (AD) is leading cause of death among older characterized by neurofibrillary tangles, oxidative stress, progressive neuronal deficits, and increased levels of amyloid-β (Aβ) peptides. Cholinergic treatment could be the best suitable physiological therapy for AD. Calcitonin gene-related peptide (CGRP) is a thirty-seven-amino acid regulatory neuropeptide resulting from different merging of the CGRP gene, which also includes adrenomedullin, amylin, calcitonin, intermedin, and calcitonin recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 64 publications
1
54
0
Order By: Relevance
“…Evidence has been provided to recommend that MAPK might be contributing to the initiation of NF‐κB in the cytoplasm just as transactivation potential alteration in the nucleus. [ 43,44 ] As the outflow of these inflammatory mediators is regulated by NF‐κB, blocking transcriptional action of NF‐κB might be a significant focus for inflammatory response treatment. Our research propose that the inhibition of MAPK pathways by embelin might be a significant action underlying the weakening of paraquat‐prompted NF‐κB transcriptional action.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been provided to recommend that MAPK might be contributing to the initiation of NF‐κB in the cytoplasm just as transactivation potential alteration in the nucleus. [ 43,44 ] As the outflow of these inflammatory mediators is regulated by NF‐κB, blocking transcriptional action of NF‐κB might be a significant focus for inflammatory response treatment. Our research propose that the inhibition of MAPK pathways by embelin might be a significant action underlying the weakening of paraquat‐prompted NF‐κB transcriptional action.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the above research on wogonin obviously show its antiarthritis protective impacts. Because of its antioxidant characteristics, Wogonin is considered to produce its activity …”
Section: Discussionmentioning
confidence: 99%
“…In fact, miR‐21 is upregulated in diverse tumors and plays a potential role in the angiogenesis of cancers (Zhao et al, ). These results indicate a role for miRNAs in lung tissues and plasma as molecular predictors of lung cancer development and aggressiveness and have theoretical and clinical implication for lung cancer management (Gupta et al, ; Rapalli et al, ; Singh et al, ).…”
Section: Development Of Renin–angiotensin–aldosterone/mas Receptor Axismentioning
confidence: 88%
“…A study showed that cigarette smoke or direct nicotine inhalation inhibits the expression of angiotensin‐converting enzyme 2 in multiple organs and cell types. In the lung, cigarette smoke (6 cigarettes/day, 12 weeks) inhibited the expression of both angiotensin‐converting enzyme 2 and mas receptor mediate beneficial effects (Gupta et al, ; Oakes, Fuchs, Gardner, Lazartigues, & Yue, ; Singh et al, ). Reports have revealed that ACE2 may have both positive and negative roles in cancer therapies, and it has been identified as an inhibitor of cancer cell growth, metastasis, and angiogenesis in lung cancer (Feng et al, ).…”
Section: Development Of Renin–angiotensin–aldosterone/mas Receptor Axismentioning
confidence: 99%